Can it be prevented this time? The role of profits in banking regulation - Lorenzo Esposito; Giuseppe Mastromatteo (Levy Economics Institute of Bard College, 2023)
Since the nineties, crises have punctuated financial markets, shattering the conventional wisdom about how these markets work and how to regulate them, and forcing a deep rethinking of the supervisory framework that, however, did not change much of the banks' behavior and incentives. In particular, banking regulation did not face the nexus profitability-riskiness. Based on Minsky's financial instability hypothesis, we discuss the literature on banks' profitability and its relation to the originate-to-distribute model. We also propose a different strategy for banking regulation, based on a profitability cap that prevents financial innovation from overwhelming supervision. Finally, we discuss the data for the US case, confirming the importance of profitability as a signal of incoming troubles and the possibility of using the profitability cap to greatly simplify banking regulation.
Keywords: G01; G28; 330; banking regulation; financial stability; Minsky; Basel 3; profitability